Mitigating Ammonia and Greenhouse Gaseous Emission From Arable Land by Co-application of Zeolite and Biochar - Ali, Awais; Ali, Muhammad Fraz; Javed, Talha; Abidi, Syed Hussain; Syed, Quratulain; Zulfiqar, Usman; Alotaibi, Saqer S.; Siuta, Dorota; Adamski, Robert; Wolny, Paweł (Frontiers in Plant Science, 2022)
Intensive use of chemical fertilizers in arable farming dramatically increased environmental pollution through anthropogenic ammonia (NH3) and greenhouse gaseous emissions. An experiment was conducted to assess the mitigating effects of sole or combined application of zeolite with biochar on gaseous emissions from arable land. For this purpose, zeolite (clinoptilolite) was mixed with different doses of biochar and applied along with recommended dose of chemical fertilizer (NPK @ 150, 100 and 60 kg ha-1, respectively) on arable land in years 2013-14 and 2014-15. Immediately after application, these were incorporated into top 10 cm of soil layer and wheat was sown. Treatments were: C = Control, Z = Zeolite @ 5 t ha-1, B1Z = Biochar @ 3 t ha-1 + Zeolite @ 5 t ha-1, B2Z = Biochar @ 6 t ha-1+ Zeolite @ 5 t ha-1, B3Z= Biochar @ 9 t ha-1+ Zeolite @ 5 t ha-1. Randomly ten soil samples from each plot was taken at depth of 0-15 cm and mixed and stored in a freezer at -18 °C until gaseous analysis in order to prevent N transformations. Each soil sample was analyzed for emission of NH3, CO2 and CH4 by using Selected Ion Flow Tube Mass Spectrometer (SIFT-MS). Co-application of zeolite and biochar reduced NH3 and CH4 emissions by on average 87 and 58% compared to control, respectively. However, CO2 emission was increased by 104% relative to the control. The NH3 emission was decreased by on average 61, 78, 90 and 92% by Z, B1Z, B2Z and B3Z treatments compared to control. Similarly, the decrement in CH4 emission was 47, 54, 55 and 65%. In contrast, increment in CO2 emission was 42, 110 and 160% for B1Z, B2Z and B3Z, respectively while interestingly a reduction of 12% was observed in Z treatment. Besides, co-application of zeolite and biochar at highest dose (B3Z) improved soil chemical properties like soil EC, OM, total N as well as available P and K relative to zeolite alone. It is concluded that combined application of zeolite and biochar can mitigate NH3 and greenhouse emissions and improve soil chemical characteristics.